STUB1 suppresses paclitaxel resistance in ovarian cancer through mediating HOXB3 ubiquitination to inhibit PARK7 expression - Laigang Zhao; HanLin Yang; Yuanmei Wang; Shuang Yang; Qisi Jiang; Jun Tan; Xing Zhao; Dan Zi (Communications Biology)
Abstract Paclitaxel (PTX) is a first-line drug for ovarian cancer (OC) treatment. However, the regulatory mechanism of STUB1 on ferroptosis and PTX resistance in OC remains unclear. Genes and proteins levels were evaluated by RT-qPCR, western blot and IHC. Cell viability and proliferation were measured by CCK-8 and clone formation. The changes of mitochondrial morphology were observed under a transmission electron microscope (TEM). Reactive oxygen species (ROS), iron, malondialdehyde (MDA) and glutathione (GSH) were measured using suitable kits. The interactions among STUB1, HOXB3 and PARK7 were validated using Co-IP, and dual luciferase reporter assay. Our study found that STUB1 was decreased and PARK7 was increased in tumor tissue, especially from chemotherapy resistant ovarian cancer tissue and resistant OC cells. STUB1 overexpression or PARK7 silencing suppressed cell growth and promoted ferroptosis in PTX-resistant OC cells, which was reversed by HOXB3 overexpression. Mechanistically, STUB1 mediated ubiquitination of HOXB3 to inhibit HOXB3 expression, and HOXB3 promoted the transcription of PARK7 by binding to the promoter region of PARK7. Furthermore, STUB1 overexpression or PARK7 silencing suppressed tumor formation in nude mice. In short, STUB1 promoted ferroptosis through regulating HOXB3/PARK7 axis, thereby suppressing chemotherapy resistance in OC.